2016
DOI: 10.1038/ncomms12029
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and monocytes synergistically promote the transition from acute to chronic pain after nerve injury

Abstract: Microglia and peripheral monocytes contribute to hypersensitivity in rodent models of neuropathic pain. However, the precise respective function of microglia and peripheral monocytes has not been investigated in these models. To address this question, here we combined transgenic mice and pharmacological tools to specifically and temporally control the depletion of microglia and monocytes in a mouse model of spinal nerve transection (SNT). We found that although microglia and monocytes are required during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
257
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(287 citation statements)
references
References 54 publications
20
257
4
2
Order By: Relevance
“…Typically, clodronate liposomes were used to deplete various kinds of macrophage/monocyte [22,23], such as primitive macrophages [24] microglia [25], Kupffer cells [26], alveolar macrophage [27], monocytes [25], tumor-associated macrophages [28,29]. Therefore, in this study, we packaged Fasudil in liposomes to realize the specific 4 targeting to macrophages/monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, clodronate liposomes were used to deplete various kinds of macrophage/monocyte [22,23], such as primitive macrophages [24] microglia [25], Kupffer cells [26], alveolar macrophage [27], monocytes [25], tumor-associated macrophages [28,29]. Therefore, in this study, we packaged Fasudil in liposomes to realize the specific 4 targeting to macrophages/monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…4) The time course of the PNIinduced SDH microgliosis in mice was revealed to be that microglia number increased from day 3, peaked at 1 week and declined later, which is almost similar to the temporal pattern of microgliosis reported in previous studies. 11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI). The early phase proliferation is consistent with several previous papers, 11,13) but the later phase is controversial.…”
Section: Discussionmentioning
confidence: 87%
“…ATP is released by injured dorsal horn neurons [90], whereupon microglial purinergic receptors are activated, leading to microglial proliferation and neuropathic pain [91-94, 95•]. The apparent reduction in the importance of microglial activity in the later stages of neuropathic pain models has led to the suggestion that microgliosis and inflammatory mediator production may be most important in the initiation of hypersensitivity and promoting the transition to chronic pain [96].…”
Section: Changes In the Spinal Cordmentioning
confidence: 99%